KAJIAN PENGEMBANGAN SEKTOR PERIKANAN DI KABUPATEN SAMBAS PERSPEKTIF EKONOMI SYARIAH - Sumar’in Sumar’in; Reo Zaputra (Jurnal Ekonomi dan Bisnis, 2023)
The fisheries sector should be a mainstay in Indonesia's development, because so far the fisheries sector is considered to have been proven as a sector that is able to survive in critical situations and is able to provide food (a source of fish protein) for the community, a source of income, and at the same time absorb a large number of workers. . Meanwhile, Sambas Regency has one sub-district which is considered a central place for trading and catching marine fish, namely the Pemangkat sub- district which must be developed. The type of research used is descriptive research and library research. Based on the results of data analysis and discussion, it can be concluded that in carrying out regional government development, including in the fisheries sector, it should prioritize moral and justice aspects. Because creating prosperity in society is the obligation of all economic agents